1999
DOI: 10.1034/j.1600-051x.1999.261006.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of medical status and physical fitness with periodontal disease

Abstract: To determine the possible associations of medical status and physical fitness with periodontal disease, a cross-sectional study was conducted. The subjects were 517 males and 113 females aged 23 to 83 years who participated in a multiphasic health test at the Aichi Prefectural Center of Health Care, Japan, from 1992 to 1997. Their periodontal status was assessed by means of the CPITN scoring system. To assess the strength of associations between the examined factors and the score, odds ratios were computed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 39 publications
16
121
2
6
Order By: Relevance
“…In addition, chewing ability may be an independent predictor of physical fitness measurements in the elderly (5 (2). This is supported by recent investigations, which found associations between impaired lipid metabolism and periodontal disease (6)(7)(8)(9)(10). Furthermore, atherosclerotic diseases such as cardiovascular diseases have recently been associated with periodontal disease (11,12).…”
Section: Periodontitis Has Been Referred To As the Sixth Complicationsupporting
confidence: 63%
See 2 more Smart Citations
“…In addition, chewing ability may be an independent predictor of physical fitness measurements in the elderly (5 (2). This is supported by recent investigations, which found associations between impaired lipid metabolism and periodontal disease (6)(7)(8)(9)(10). Furthermore, atherosclerotic diseases such as cardiovascular diseases have recently been associated with periodontal disease (11,12).…”
Section: Periodontitis Has Been Referred To As the Sixth Complicationsupporting
confidence: 63%
“…Whether atherogenic factors other than hyperglycemia are linked with periodontal damage, however, is still being debated, and previous studies have reported inconsistent results (6)(7)(8)(9)(10)(13)(14)(15)(16)(17)(18)(19)(20)(21) …”
Section: Periodontitis Has Been Referred To As the Sixth Complicationmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However the RBC count remains unchanged between all the three groups . Also ESR provides a multifactorial measure of a systemic response to a disease .And in our study ESR was seen higher in periodontits group compared to ginigivitis or healthy group.However this parameter of inflamation seems to be of limited use as a diagonistic tool in periodontitis to measure systemic involvement.…”
Section: Means Of the Hematocrit Values In The Three Groupsmentioning
confidence: 93%
“…If these clinical diagnostic tests could be applied to the screening of periodontal disease, the problems described above could be overcome (4)(5)(6)(7)(8)(9). Some reported studies have demonstrated a correlation between blood test parameters and periodontal status.…”
Section: Introductionmentioning
confidence: 99%